ADA YANG MANIS DI TIMUR NUSANTARA? KOSMOPOLITANISME TANAMAN TEBU DALAM HISTORIOGRAFI INDONESIA - Ridhoi, Ronal (Universitas Negeri Malang, 2021)
This paper tries to remind readers about the history of sugarcane in the archipelago and its transnationalization. This crop, which is actually endemic on Eastern Indonesia, was famous in the market world since Europeans